Differential impact of cytochrome 2C9 allelic variants on clopidogrel-mediated platelet inhibition determined by five different platelet function tests - Gremmel, Thomas; Kopp, Christoph W.; Seidinger, Daniela; Koppensteiner, Renate; Panzer, Simon; Sunder-Plassmann, Raute; Mannhalter, Christine; Steiner, Sabine (International journal of cardiology, 2013)
The antiplatelet effect of clopidogrel is subject to considerable inter-individual variations. In vitro high on-treatment residual platelet reactivity (HRPR) has been linked to cytochrome P450 (CYP) 2C19*2 carriage, and both were significantly associated with the occurrence of adverse events after coronary stenting. It has been shown that besides CYP2C19, CYP2C9 is involved in the hepatic biotransformation of clopidogrel to its active metabolite. Consequently, CYP2C9 polymorphisms may also affect the extent of clopidogrel-mediated platelet inhibition. We therefore studied the influence of CYP2C9 allelic variants on clopidogrel-mediated platelet inhibition as assessed by 5 platelet function tests. On-clopidogrel residual platelet reactivity was assessed by light transmission aggregometry (LTA), the VerifyNow P2Y12 assay, the VASP assay, multiple electrode aggregometry (MEA), and the Impact-R in 288 patients after angioplasty and stenting for cardiovascular disease. Allelic variants CYP2C9*2 and *3 were determined using a RealTime PCR assay. A significantly higher on-treatment platelet reactivity was found for patients with loss-of-function (LOF) status (wt/*3, *2/*2, *3/*3) compared to normal-function genotype (wt/wt, wt/*2) using the VerifyNow assay (P=0.01). An in trend increase was seen with LTA (P=0.06) while results did not differ for the VASP assay, MEA or the Impact-R. Further, in univariate and multivariable logistic regression analysis the LOF genotype was associated with HRPR determined by the VerifyNow P2Y12 assay (P=0.02) but not by any other assay. Results from the VerifyNow P2Y12 assay are significantly influenced by CYP2C9 LOF variants leading to decreased clopidogrel-mediated platelet inhibition and an increased rate of HRPR.